PENCEGAHAN KEKERASAN SEKSUAL BERBASIS MASJID DALAM MEWUJUDKAN MASJID RAMAH PEREMPUAN DAN ANAK - Ch, Mufidah; Rouf, Abd. (EGALITA, 2024)
Abstract Cases of sexual violence have recently occurred frequently in the public sector, such as workplaces, public services, educational institutions, and even places of worship like mosques. The Indonesian Mosque Council (DMI), as an authoritative institution, aims to create mosques that are friendly to women and children to address this issue. This hope is carried out by the leadership of the Indonesian Mosque Council from the central level to the regions. This research aims to examine the responses and prevention models of sexual violence that will be implemented by the Regional Leadership of the Indonesian Mosque Council (PD DMI) in Malang Regency in realizing mosques that are friendly to women and children. This research is a field study with a phenomenological qualitative approach. Primary data sources include the PD DMI of Malang Regency, the Expert Council of PD DMI of Malang Regency, the management of the Great Mosque and the Grand Mosque, as well as the Department of Empowerment of Muslimah, Children, and Families (PPMAK) at PD DMI of Malang Regency. Meanwhile, the secondary data consists of literature books, journals, laws, and related regulations obtained from interviews and documentation. The results obtained indicate that realizing a mosque that is friendly to women and children is not only achieved through the provision of information and education on the prevention of sexual violence but also includes the establishment of regulations, integration of themes in Friday sermons, education through study circles, infrastructure improvements, the establishment of family corners, and collaboration with relevant institutions Keywords: Indonesian Mosque Council; Sexual Violence; Women and Children Friendly MosqueAbstrak Kasus kekerasan seksual belakangan sering terjadi di sektor publik seperti tempat kerja, layanan publik, lembaga pendidikan, bahkan terpat peribadatan seperti masjid. Dewan Masjid Indonesia (DMI) sebagai lembaga berwenang ingin mewujudkan masjid ramah perempuan dan anak untuk mengatasi kasus tersebut. Harapan ini dilakukan oleh pimpinan Dewan Masjid Indonesia di tingkat pusat sampi daerah. Penelitian ini bertujuan untuk melihat respons dan model pencegahan kekerasan seksual yang dilakukan oleh Pimpinan Daerah Dewan Masjid Indonesia (PD DMI) Kabupaten Malang dalam mewujudkan masjid ramah perempuan dan anak. Penelitian ini termasuk penelitian lapangan dengan pendekatan kualitatif fenomenologis. Sumber data primer meliputi PD DMI Kabupaten Malang, Dewan Pakar PD DMI Kabupaten Malang, Takmir Masjid Besar dan Masjid Agung, serta Departemen Pemberdayaan Potensi Muslimah, Anak dan Keluarga (PPMAK) pada PD DMI Kab. Malang. Sedangkan data skunder berupa buku literatur, jurnal, undang-undang, dan peraturan terkait yang diperoleh dari wawancara dan dokumentasi. Hasil yang diperoleh yaitu dalam mewujudkan masjid ramah perempuan dan anak tidak hanya dilakukan melalui pemberian informasi dan edukasi mengenai pencegahan kekerasan seksual, tetapi juga mencakup pembentukan regulasi, integrasi tema dalam khutbah Jum'at, pendidikan melalui pengajian, perbaikan infrastruktur, pendirian family corner, serta kolaborasi dengan lembaga-lembaga terkait. Kata Kunci: Dewan Masjid Indonesia; Kekerasan Seksual; Masjid Ramah Perempuan dan Anak